The Regional Hydroclimate Response to Stratospheric Sulfate Geoengineering and the Role of Stratospheric Heating. Issue 23 (5th December 2019) - Simpson, I. R.; Tilmes, S.; Richter, J. H.; Kravitz, B.; MacMartin, D. G.; Mills, M. J.; Fasullo, J. T.; Pendergrass, A. G.
Abstract: Geoengineering methods could potentially offset aspects of greenhouse gas‐driven climate change. However, before embarking on any such strategy, a comprehensive understanding of its impacts must be obtained. Here, a 20‐member ensemble of simulations with the Community Earth System Model with the Whole Atmosphere Community Climate Model as its atmospheric component is used to investigate the projected hydroclimate changes that occur when greenhouse gas‐driven warming, under a high emissions scenario, is offset with stratospheric aerosol geoengineering. Notable features of the late 21st century hydroclimate response, relative to present day, include a reduction in precipitation in the Indian summer monsoon, over much of Africa, Amazonia and southern Chile and a wintertime precipitation reduction over the Mediterranean. Over most of these regions, the soil desiccation that occurs with global warming is, however, largely offset by the geoengineering. A notable exception is India, where soil desiccation and an approximate doubling of the likelihood of monsoon failures occurs. The role of stratospheric heating in the simulated hydroclimate change is determined through additional experiments where the aerosol‐induced stratospheric heating is imposed as a temperature tendency, within the same model, under present day conditions. Stratospheric heating is found to play a key role in many aspects of projected hydroclimate change, resulting in a general wet‐get‐drier, dry‐get‐wetter pattern in the tropics and extratropical precipitation changes through midlatitude circulation shifts. While a rather extreme geoengineering scenario has been considered, many, but not all, of the precipitation features scale linearly with the offset global warming. Plain Language Summary: This study examines the model‐projected hydroclimate changes, relative to present day, that occur when greenhouse gas‐driven warming at the end of the 21st century is offset by the injection of sulfate aerosols into the stratosphere. A high greenhouse gas emissions scenario is considered, and the aerosol injection strategy is designed to maintain the global mean temperature, the equator‐to‐pole temperature gradient, and the interhemispheric temperature gradient. The leading order response in the tropics is a wet‐get‐drier, dry‐get‐wetter pattern with substantial drying over India, Amazonia, and parts of Africa. In the midlatitudes, precipitation changes occur in association with shifts of the midlatitude westerlies. Additional experiments are used to assess the role of the dynamical response to warming of the lower stratosphere in producing these responses, and it is found that the dynamical response to warming of the lower stratosphere does, indeed, play an important role in the simulated hydroclimate changes. Key Points: GLENS geoengineering simulations exhibit substantial precipitation changes, relative to present day Stratospheric heating plays a key role in many of the simulated precipitation changes Stratospheric heating generally leads to drying in many wet tropical regions